Episode 5: looking to the future: university vaccinations, recycling smart on campus, and pandemic study abroad - Tufts Daily (Tufts Archival Research Center, 2021)
On this Rewind episode, Governor Charlie Baker announced Wednesday that vaccines will be available to Massachusetts residents 16 and older on April 19; what does that mean for when and how Tufts students can be vaccinated? Also, we discuss a Green Fund project aimed at improving recycling habits on campus and how students are adjusting their plans to study abroad amid the pandemic.